Multicomponent Betti reaction affords covalent organic framework nanoreactor for palladium-catalyzed nitroarene reduction - Salarinejad, Neda; Dinari, Mohammad; Lins, Jonas; Gutmann, Torsten; Chae, Keun Hwa (Communications Chemistry)

Cell stress and phase separation stabilize the monomeric state of pseudoisocyanine chloride employed as a self-assembly crowding sensor - Pollak, Roland; Koch, Leon; König, Benedikt; Ribeiro, Sara S.; Samanta, Nirnay; Huber, Klaus; Ebbinghaus, Simon (Communications Chemistry)
Abstract Cellular stress and ageing involve an increase in crowding and aggregation of amylogenic proteins. We here investigate if crowding is the intrinsic cause of aggregation and utilise a previously established non-protein aggregation sensor, namely pseudoisocyanine chloride (PIC). PIC shows fibrillization in cells into a highly fluorescent J-aggregated state and is sensitive to crowding. Surprisingly, cell stress conditions stabilise the monomeric rather than the aggregated state of PIC both in the cytoplasm and in stress granules. Regarding the different physiochemical changes of the cytoplasm occurring upon cell stress, involving volume reduction, phase separation and solidification, the intrinsic crowding effect is not the key factor to drive associated self-assembly processes.

Time-dependent vibrational sum-frequency generation spectroscopy of the air-water interface - Ojha, Deepak; Kaliannan, Naveen Kumar; Kühne, Thomas D. (Communications Chemistry)